ChemInform Abstract: Preparations and Reactions of SF5‐Substituted Aryl and Heteroaryl Derivatives via Mg and Zn Organometallics. Issue 4 (31st January 2013) - Frischmuth, Annette; Unsinn, Andreas; Groll, Klaus; Stadtmueller, Heinz; Knochel, Paul
Abstract Organometallic protocols, compatible with the sensitive ‐SF5 group are exploited for the preparation of a variety of SF5‐substituted aryl and heteroaryl derivatives.